Just one word - plastics [organic semiconductors]. - Moore, S.K.
Organic semiconductors could put cheap circuits everywhere and make flexible displays a reality. The author considers these prospects, discussing their implementation and the fabrication technology involved.
Keywords: OLEDs; Fabrication technology; Flexible circuits; Flexible displays; Inkjet printing; Low cost circuits; Organic semiconductors; Plastic sheet; Printing technology; Self-assembled monolayer